1993
DOI: 10.3354/meps092099
|View full text |Cite
|
Sign up to set email alerts
|

Marine cyanophages infecting oceanic and coastal strains of Synechococcus: abundance, morphology, cross-infectivity and growth characteristics

Abstract: Eight different phycoerythrin-and phycocyanin-containing strains of Synechococcus spp. and 1 strain of Anacystis marina were screened against 29 natural virus communities taken from 3 locations in south Texas (USA) coastal waters, at different times of the year. In add~tion, 1 sample was screened from Peconic Bay, New York, USA. Cyanophages were detected in all samples, but the frequency with which they were detected and their abundance depended upon the strain of Synechococcus sp. that was screened. Viruses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
349
5
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(372 citation statements)
references
References 16 publications
13
349
5
2
Order By: Relevance
“…For example, if prokaryote and virus abundances varied systematically with another environmental co-factor during a transect, then this would potentially influence the inferred relationship between virus and prokaryote abundances. In that same way, variation in environmental correlates, including temperature and incident ration, may directly modify virus life history traits [20,44]. Likewise, some of the marine survey datasets examined here constitute repeated measurements at the same location (e.g., at the Bermuda Atlantic Time-series Study (BATS)).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if prokaryote and virus abundances varied systematically with another environmental co-factor during a transect, then this would potentially influence the inferred relationship between virus and prokaryote abundances. In that same way, variation in environmental correlates, including temperature and incident ration, may directly modify virus life history traits [20,44]. Likewise, some of the marine survey datasets examined here constitute repeated measurements at the same location (e.g., at the Bermuda Atlantic Time-series Study (BATS)).…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches, relying on conceptual models or other indirect measurements, suggested that losses from viral lysis were in the same range as those attributed to protist grazing (Proctor and Fuhrman, 1990;Suttle and Chan, 1993). For a mesocosms experiment, for example, Fuhrman and Noble (1995) showed that viruses and protists were responsible for similar amounts of bacterial loss (they specifically account for 70-75% of the total apparent mortality with these two mechanisms).…”
Section: The Role Of Viruses In the Food Webs The Microbial Loopmentioning
confidence: 99%
“…The "viral loop" was not considered as an independent process, but rather as a component of the "microbial loop, " and early estimates suggested that as much as 25% of the primary production in the ocean flows through this loop (Wilhelm and Suttle, 1999). For its capacity to disrupt the microbial loop, it was even advanced that the viral loop leads to a "futile cycle" or "short circuit" of carbon flow, resulting in an energy loss by respiration as the cycle turns (Suttle and Chan, 1993;Azam et al, 1994), since bacteria do not convert DOM into biomass with a 100% efficiency.…”
Section: The Viral Loopmentioning
confidence: 99%
See 2 more Smart Citations